Experimental evaluation of cutting force parameters applying mechanistic model in orthogonal milling - Coelho,R. T. (2003)
There have been considerable efforts in research to understand the basics of chip formation. Models developed for turning and adapted to milling, yield reasonable results, except in some particular applications. This work develops an experimental method capable of providing cutting data in a fast and reliable way to evaluate the specific cutting presure(Ks), the friction coefficient (m) and the ploughing/elastic forces (F E). Different models for the cutting force can be tested, and the coefficient of determination (R²) assesses the adequacy of models. The particular adopted model, used to test the experimetal method hereby proposed, resulted in a good agreement with experimental data, expressed by R² values very close to the unity